Considering strategically the issue of disability in the classroom: an exploratory - Bianquin, Nicole; Sacchi, Fabio; Besio, Serenella (Formazione & insegnamento, 2018)
Tackling at school a sensitive subject like disability requires a willingness and awareness of the teachers about the importance of dealing with this subject and about the educational and didactic implications of such programs have on children. The Italian school, characterized by a long tradition of including children with disabilities, needs the structuring of specific proactive interventions, which provide children with a deeper understanding of disability. The design of such educational interventions can require a great commitment to teachers because it recalls a plurality of factors including those related to the identification of appropriate teaching strategies, the choice of possible mediators and the questioning about the availability, intentionality and opportunity to propose children a theme considered ‘sensitive’. With the aim of knowing what the considerations of the teachers are, it was designed a sequential-exploratory research, composed by a qualitative and quantitative phase.